2016
DOI: 10.1016/j.celrep.2016.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Low CD38 Identifies Progenitor-like Inflammation-Associated Luminal Cells that Can Initiate Human Prostate Cancer and Predict Poor Outcome

Abstract: SUMMARY Inflammation is a risk factor for prostate cancer, but the mechanisms by which inflammation increases that risk are poorly understood. Here, we demonstrate that low expression of CD38 identifies a progenitor-like subset of luminal cells in the human prostate. CD38lo luminal cells are enriched in glands adjacent to inflammatory cells and exhibit epithelial nuclear factor κB (NF-κB) signaling. In response to oncogenic transformation, CD38lo luminal cells can initiate human prostate cancer in an in vivo t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
129
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 105 publications
(140 citation statements)
references
References 54 publications
(117 reference statements)
10
129
0
1
Order By: Relevance
“…4 Gene expression analysis of CD38lo cells revealed enrichment of many inflammatory-related genes, and immunohistochemical staining of human prostate tissue confirmed that CD38lo luminal cells are predominantly localized in glands adjacent to inflammation.…”
mentioning
confidence: 80%
See 3 more Smart Citations
“…4 Gene expression analysis of CD38lo cells revealed enrichment of many inflammatory-related genes, and immunohistochemical staining of human prostate tissue confirmed that CD38lo luminal cells are predominantly localized in glands adjacent to inflammation.…”
mentioning
confidence: 80%
“…Serial biopsies of benign human prostate tissue containing chronic inflammation may help uncover the precise order of events involved in PIA. Interestingly, our gene expression analysis revealed that PIA-like cells upregulate several pro-inflammatory cytokines and chemokines, 4 suggesting that PIA-like cells may actively recruit inflammation. The assays used to measure progenitor activity require that epithelial cells be removed from their native environment, dissociated into single cells, and grown in a culture system lacking several of the key cell types found in the prostate microenvironment including inflammatory cells.…”
mentioning
confidence: 89%
See 2 more Smart Citations
“…Results from a 2015 study using a Pten – Tp53 -null mouse model of prostate cancer also demonstrate that luminal cells can be prostate cancer progenitors: culturing organoids derived from luminal cells initiated adenocarcinoma or tumours with multilineage histological phenotypes 91 . Liu and colleagues 92 discovered that low expression of CD38 could be used as a biomarker to identify progenitor-like, inflammation-associated luminal cells that can initiate human prostate cancer. They demonstrated that CD38-low luminal cells expressing both basal (K5 and p63) and luminal (K8) markers were enriched by fourfold to fivefold in organoid formation compared with CD38-high luminal cells.…”
Section: Application In Urological Diseasesmentioning
confidence: 99%